PROGRAM LINGKAR BACA CERIA SEBAGAI UPAYA PENINGKATAN KEMAMPUAN MEMBACA AWAL SISWA SEKOLAH DASAR - Parsyllah Minallah, Ninda; Rahman Hakim, Arif; Habibuddin; Nadiatul Soleha, Ria; Ulya, Manzilatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading difficulty among lower-grade elementary school students, such as letter recognition and reading fluency, remains a pivotal challenge in primary education. This study aims to describe the efforts to develop students' early reading skills at SD Negeri 6 Selong through the